PENGARUH PERBEDAAN WAKTU PANEN TERHADAP KARAKTERISTIK KIMIA BIJI KECIPIR - Rizki Dwi Setiawan; Fransiska Rungkat Zakaria; Azis Boing Sitanggang; Endang Prangdimurti; Dede Robiatul Adawiyah; Erniati Erniati (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
In Indonesia, the utilization of winged bean seeds as a food source is very limited. Currently there is inadequate information on the characteristics of the seeds, especially the chemical properties associated with its maturity. This research aimed to analyze the chemical properties of winged bean obtained from different harvesting time. Three different harvesting times were investigated, i.e. eight (K1), twelve (K2), and as six (6) weeks after the first flowering stage as a control. K1 and K2 were dried at 40°C (24 h) to mimic the conventional preparation of beans practiced in Indonesia, while K3 was unripe seeds commonly consumed fresh thus it is analyzed as fresh seeds. K1 and K2 have water content between 12.3-13.0% (wb), ash content 4.7-4.8% (db), lipid content 13.4-15.4% (db), protein content 38.9-40.7% (db), carbo-hydrate content 40.8-41.0% (db), total phenolic content 7.6 and 5.3 mg GAE/g (db), antioxidant activity (IC50) 558.3 and 511.1 µg/mL, starch content 25.6-29.1%, reducing sugar content 1.3-1.7 mg/g. Mean-while, the unripe winged bean seeds (K3) has water content of 75.5% (wb), ash content 5.0% (db), protein content 19.6% (db), carbohydrate content 68.4% (db), total phenolic content of 59.4 mg GAE/g (db), anti-oxidant activity (IC50) 485.6 µg/mL, starch content 7.2% and reducing sugar 5.4 mg/g. Based on these che-mical properties and time efficiency, harvesting winged bean at 8 weeks (K1) was sufficient to produce winged bean potential as protein source, as well as a potential functional foods with good antioxidant acti-vity, total phenolic content, low starch and reducing sugar.